2011
DOI: 10.1590/s0036-46652011000400009
|View full text |Cite
|
Sign up to set email alerts
|

Acute inflammatory demyelinating polyradiculoneuropathy (Guillain-Barré syndrome) following dengue fever

Abstract: SUMMARYThis paper reports a case of dengue in a six-year-old female child who suddenly developed excruciating headaches, fever, myalgia and paresis. Laboratory examinations included blood count, platelet count, biochemical tests (BUN, creatinine, aminotransferases, and total bilirubin and bilirubin fractions) and specific IgM titers (enzyme-immunoassay with recombinant tetravalent dengue). After ten days of hospitalization and having already been in a home environment, a new clinical image emerged, characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Zika fetal disorder accounts for the aforementioned complexities along with the neonatal neurological impairment during pregnancy. GBS has been observed to sporadically follow dengue viral infection910 but is apparently more severe in the case of ZIKV due to the incidence of teratogenic lesions11. ZIKV has been identified by PCR in fetuses, and Zika virus particles have been detected by electron microscopy in the fetal central nervous system in high concentrations5.…”
mentioning
confidence: 99%
“…Zika fetal disorder accounts for the aforementioned complexities along with the neonatal neurological impairment during pregnancy. GBS has been observed to sporadically follow dengue viral infection910 but is apparently more severe in the case of ZIKV due to the incidence of teratogenic lesions11. ZIKV has been identified by PCR in fetuses, and Zika virus particles have been detected by electron microscopy in the fetal central nervous system in high concentrations5.…”
mentioning
confidence: 99%
“…It is characterized by ascending paralysis, areflexia, and sensory changes [6]. It is the most common peripheral nervous system complication of dengue fever, and is usually reported during the recovery phase of the illness [12].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with GBS can present with a wide spectrum of clinical manifestations ranging from mild self-limiting disease to acute fulminant cases with respiratory paralysis [5]. Compared with other infections such as Campylobacter jejuni and cytomegalovirus, dengue fever is an uncommon antecedent of GBS and only a few cases have been reported [6789]. Here, we report two cases of dengue fever complicated by GBS.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with previous studies 14,15 . Earlier clinical case studies reported dengue preceding GBS [20][21][22][23][24][25][26] . Our findings further showed that there is a cross-correlation between GBS and dengue cases.…”
Section: Discussionmentioning
confidence: 99%